Pengaruh Kualitas, Harga, eWOM, dan Citra Merek Terhadap Minat Beli Konsumen UMKM Kuliner - Melani Kadar; Mardiana R; Irfan Hasandi; Caesar Rosyad Achmadi; Saifan Ali Fazila (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2025)
Digital marketing has become an increasingly important strategic tool for culinary MSMEs in attracting consumer interest, especially with the use of social media and other digital platforms. One that is currently popular is the assessment of direct customer reviews on digital platforms, namely eWOM (electronic word of mouth). This study aims to analyze the influence of electronic word of mouth (eWOM), product price, product quality, and brand image on consumer purchasing interest in culinary MSMEs in Jambi City. This study uses a survey method by distributing questionnaires to 385 respondents who are consumers of culinary MSMEs in Jambi City. The data collected was analyzed using the Partial Least Squares (PLS) method to test the relationship between variables. The results of the study showed that the eWOM and brand image have a significant effect on purchasing interest. Then, product price and product quality have a significant effect on brand image, while indirectly, the product price and product quality have a significant effect on consumer purchasing interest through the brand image.